Língua wauja (arawak): uma descrição fonológica e morfossintática - Postigo, Adriana Viana [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The aim of this thesis is to analyse the phonological and morphosyntathic aspects of Wauja language. Wauja is part of the Arawak linguistic family and is spoken by approximately 410 people living in Piyulaga village, located in the Xingu Indigenous Park, state of Mato Grosso. This work presents information about Wauja people, their linguistic situation, some considerations on the school of the village, and a presentation of the theoreticalmethodological framework applied to the collecting of field data. The bibliographical review contains the first notes published about Wauja, word lists, early studies of the language, and the genetic affiliation of the Arawak family. In the phonological analysis it is described consonantal, vocalic and approximant segments, syllabic patterns, stress, nasality, morphophonological processes, and some considerations on the orthographical conventions used in the school of the village. Concerning the morphology, this thesis describes the following grammatical categories: nouns, verbs, adjectives, adverbs, pronouns, interrogative forms and quantifiers. In the syntactical analysis, this dissertation presents the kinds of predicates, declarative, interrogative, and imperative sentences. It also presents complex sentences, which can be coordinate (conjunctive, adversative and disjunctive) and subordinated (complement, relative, adverbial, temporal and causal). This thesis therefore aims to contribute to the documentation, description and analysis of Brazilian indigenous languages, specially the languages of Arawak family

Esta tese tem por objetivo analisar a língua wauja em seus aspectos fonológicos e morfossintáticos. A língua wauja pertence à família linguística arawak e é falada por aproximadamente 410 pessoas que vivem na aldeia Piyulaga, localizada no Parque Indígena do Xingu, no Estado de Mato Grosso. No presente trabalho, há informações sobre o povo wauja, sua situação linguística, algumas considerações sobre a escola na aldeia e, também, uma explicitação do modelo teórico-metodológico utilizado para a coleta de dados em campo. A revisão bibliográfica aborda as primeiras notícias publicadas sobre os wauja, as listas de palavras, os estudos prévios e a filiação genética da família arawak. Na análise fonológica, foram descritos os segmentos consonantais, vocálicos, aproximantes, padrões silábicos, acento, nasalidade, processos morfofonológicos e, ainda, algumas considerações sobre as convenções ortográficas utilizadas na escola da aldeia. Em relação à morfologia, a tese descreve as seguintes categorias gramaticais: nomes, verbos, adjetivos, advérbios, pronomes, formas interrogativas e quantificadores. Na análise sintática, a tese apresenta os tipos de predicados, as sentenças declarativas, interrogativas, imperativas e as orações complexas, que por sua vez, dividem-se em coordenadas (conjuntivas, adversativas e disjuntivas) e subordinadas (orações complemento, relativas, adverbiais, temporais e causais). Esta tese, portanto, busca contribuir para a documentação, descrição e análise das línguas indígenas brasileiras, em especial, as línguas da família arawak
Keywords: Linguística; Indios; Indios - Linguas; Gramática comparada e geral - Fonologia; Grammar, Comparative and general Phonology